Impact of Sitka spruce (Picea sitchensis (Bong.) Carr.) afforestation on the carbon stocks of peaty gley soils – a chronosequence study in the north of England. (14th May 2019) - Vanguelova, E I; Crow, P; Benham, S; Pitman, R; Forster, J; Eaton, E L; Morison, J I L
Abstract: This study aimed to quantify the medium-term impact of afforestation with Sitka spruce ( Picea sitchensis (Bong.) Carr.) on C stocks of peaty gley soils through a 100 year chronosequence of 40 plots in Kielder Forest, northern England. Litter layer C stocks in the afforested plots were 4.11 t C ha −1 (3.58–4.70, 95 per cent CI) compared with open moorland, which had no litter. In the organic F horizon, C stocks accumulated significantly through time at a rate of 1.3 per cent per year, with a significant difference in average C stocks by rotation (rotation 1: 49.7 t C ha −1 ; rotation 2: 24.0 t C ha −1 ) and a significant increase in horizon thickness through time (end of rotation 1: 11 cm; end of rotation 2: 6.5 cm) at a rate of 11 per cent per year ( P < 0.05). There was no significant change in C stocks through time or across different rotations in the peat (H) horizon, with the exception of a noticeable C loss during the first 30 years of first rotation. H horizon C stock, its thickness and C concentration all increased significantly ( P < 0.05) with altitude. Although soil C stocks in the mineral A horizon (0–20 cm depth) did not change significantly with any tested factors, soil C concentration significantly increased with afforested years. The average whole-profile (down to 70–100 cm depth) soil C stock rate of change with time since afforestation was not significant. These findings suggest that the high variability in C change in the peat H horizon was likely due to leaching, oxidation and decomposition processes linked with disturbance during afforestation and clearfelling. The loss of C in the peat layer during the first rotation was compensated by C accumulation in the upper organic F horizon. Over two rotations of conifer afforestation, the total C stock of the organo-mineral soils at Kielder was therefore unchanged.